Integrating Digital Feedback To Enhance Sustainable And Equitable Peer Collaborative Skills, Feedback Literacy And Reflective Practice In Undergraduate Groups: Learnings From Australian Case Studies - Emery, Kirsty; Matthews, Susan (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Flinders University (Australia) transitioned to a new learning management system facilitating access to a suite of eco-friendly digital tools, sustained by renewable energy sources. In this study, we evaluated the effectiveness of online peer feedback tools on group assessment skill development, learning processes and self-reflection within two different undergraduate student cohorts. Consistent with current theoretical knowledge in this field, we demonstrated that the implementation of effective peer feedback requires consideration of four influential factors: student characteristics, environment, learning processes and learning outcomes. Importantly, these case studies highlight the ability to readily digitalise assessment and feedback processes for undergraduate student groups, reducing hard-copy resources and enabling equitable student access via laptops, smart phones or tablets at any time. At a broader educational level, digital feedback tools such as FeedbackFruits, can be scaled-up to deliver sustainable higher education practices fostering inclusive, future-ready learning environments for the acquisition of core graduate qualities.